Flourishing Beyond Borders: Facilitating the Well-Being of Accompanying Expatriate Partners - Botha, Truida; Potgieter, Johan C.; Botha, Karel F. H. (Frontiers in Psychology, 2022)
One of the leading causes for failing at expatriate assignments is the accompanying expatriate partners’ (AEPs) unhappiness with life abroad or inability to adjust to the challenges of the host country. Strength-based therapeutic interventions have the potential to increase individuals’ mental health and well-being. The current study formed part of a multimethod study consisting of three related but independent sub-studies. The first sub-study identified the strengths of Gratitude, Curiosity and Hope to be positively associated with AEPs’ resilience and well-being. These results were used to construct a quantitative model that illustrates the interplay between these constructs. In the second sub-study, the proposed model was qualitatively reviewed by a smaller group of AEPs to inform and enrich our understanding of AEPs’ personal experiences of these constructs. In the current study, a panel of practicing psychologists who provide counselling services for South African expatriates and AEPs were asked to qualitatively review a proposed quantitative model. A cross-sectional, interpretive descriptive research design, applying purposive sampling was used to identify and recruit participants. The objective for the current study was firstly to ascertain why participants thought strengths of Gratitude, Curiosity and Hope featured so prominently in the model. Secondly, the study aimed to determine how these participants would, from their experience in working with AEPs, enhance these strengths and AEPs’ resilience in therapy, and ultimately facilitate greater well-being and successful adjustment abroad. Participants completed an online questionnaire consisting of two semi-structured, open-ended questions. The data were analyzed using primary and secondary cycle coding to ultimately develop themes. Results indicated that strengths of Curiosity, Gratitude and Hope featured prominently because these strengths include elements that form part of the process of expatriation. Participants were able to suggest practical strength-based therapeutic techniques which would assist in enhancement of strengths, resilience and ultimately well-being. It is proposed that the therapeutic techniques and approaches suggested in this study could contribute to the success rate of expatriate assignments.